PENGARUH PEMBAGIAN KERJA, DISIPLIN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PT. CITRA BUANA PRAKARSA - DESSY .; WASIMAN . (LP2MTBM MAKARIOZ, 2020)
Human resources are the main key to the successful of a company’s operationtional, so companies must maintain stabilityand improve employee performance to focused to achieved the company’s goals, particularly in property and real estateindustry which is growth by millennial generation demand. Human resources who can work professionally and consistentlyare expected to be able to produce high performance. Employee performance can be influenced by divison of work which isreflected in the division of work type and work field, work discipline is reflected by company's rules and work experience fromduration of work in an occupation. This study aims to examine the effect of division of work, work discipIine and workexperience on the employeesperformance of PT. Citra Buana Prakarsa. This study uses a purposive sampling method todetermine the number of samples. The research sample consisted of 200 employees of PT. Citra Buana Prakarsa. Data wascollected by distributing questionnaires directly and analyzed using SPSS version 25. T test result that division of work, workdiscipIine and work experience significantly influence on empIoyee performance. F test results show that division of work,work discipIine and work experience together affect the empIoyee performance.